Analysis of Employee Safety Behavior at PT BTUB to Achieve Zero Workplace Accidents - Murtasiyah, Murtasiyah; Sanafi, Muslimin (Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study explores employee safety behavior at PT BTUB in support of achieving a sustainable zero workplace accident target. Despite successfully reaching this goal in 2022, challenges remain due to persistent unsafe behaviors among employees. Using the Safe Behavior Observation (PPS) tool, the research identifies key areas of unsafe practices, including improper positioning, misuse of tools and equipment, and risky activities during high-hazard tasks. These behaviors were systematically analyzed through a descriptive quantitative approach, integrating observational data and company safety reports. The findings highlight the positive impact of a safety culture fostered through leadership, employee participation, and targeted training programs. However, the study emphasizes the need for continuous improvements in safety practices by enhancing training quality, leveraging technology for real-time safety monitoring, and fostering stronger leadership engagement. By addressing these factors, PT BTUB can further strengthen its safety management system and provide valuable insights for other organizations in high-risk industries. This research underscores the importance of behavioral interventions in creating safer work environments and achieving sustainable safety outcomes.